(untitled) (Revista de Ciências Agroveterinárias, 2007)
Dregs is an alkaline industrial residue that can be used to raise soil pH at low cost. Since it presents low Mg and high sodium amounts, it can negatively affect plant growth. This work was carried out to evaluate the speed of dregs to neutralize the soil acidity; to measure the effect of soil pH elevation due to dregs in the availability of Mg for wheat plants; and to assess the behavior of Na adsorption in different levels of soil acidity. Three experiments were set up, in the laboratory or in a greenhouse, using samples of a Haplumbrept soil. Increasing amounts of dregs were used in the first two experiments, having the following composition: 354 g Ca kg-1, 9.2 g Mg kg-1, 10.2 g Na kg-1, pH = 10.7, neutralization value of 80% and relative efficiency of 100%. The effect of Mg addition on different pH levels after dregs addition was evaluated in the wheat experiment. The reactions dealing with neutralization of soil acidity due to addition of dregs were concluded in a period smaller than three weeks after dregs application. The adsorption of Na to the negative charges and the electronic affinity of Na for the solid phase of this Haplumbrept, defined by the partition coefficient of the adsorption reaction (KP), had the behavior of a C-type isotherm and both increased with the rise of soil pH. Despite the addition of Mg having increased the wheat dry mass yield in all rates of dregs, pH increase due to the addition of industrial residue did not affect Mg availability and plant growth.